A Survey of the Phenomenological Research of Listening to Preaching (Homiletic, 2013)
The preaching literature overflows with normative definitions of preaching – preachers ought to do this, because this is what Paul, or Jesus did. The listener has been understood as a constant, whom the preacher sought to educate and persuade. Against this backdrop an interest developed in what listeners “do” with sermons. A new vein of homiletical research followed – namely the phenomenological study of what listeners “do” when hearing sermons. Within this vein is the Dutch/German practical theological research, highlighting how sermon themes, life situation, the preacher’s connectedness to the congregation, or how listeners’ personality type affect engagement with the sermon. Conversely there arose American liberal arts driven homiletics, utilizing communication or rhetorical frameworks to understand what listeners are doing. This paper reviews all the phenomenological research from both fronts, and attempts to summarize, highlight the recurring themes, and clarify the points of tension and difference therein.